ANALISIS DAMPAK KONSENSI TERHADAP KELAYAKAN PROYEK PERKERETAAPIAN - Salim, Indra Putra; Simanjuntak, Manlian Ronald A.; Sulistio, Hendrik (Politeknik Negeri Semarang, 2024)
Concession agreements have been implemented in many transportation infrastructure projects in Indonesia as a creative step by the government to meet the funding needs of transportation infrastructure projects in the country. The Jakarta-Bandung High-Speed Railway (JBHSR) is a major railway project with substantial investment. Despite securing a 50-year concession, the project has seen escalating investment costs. Nevertheless, the concession significantly impacts the feasibility of the project investment. This study examines and analyzes several factors that influence or are considered in the concession period agreement of railway projects. The research employs a qualitative descriptive method involving literature review, policy document analysis, and expert interviews. The research shows that high-speed railway projects typically have a lengthy return on investment. This is supported by the scarcity of countries globally where such projects have achieved both investment recovery and profitability. Regarding the 50-year concession for the JBHSR Project, it becomes inconsequential when construction issues arise, impacting costs and investment scale. Therefore, a review and reevaluation of the concession period is necessary. Furthermore, certain considerations need to be taken into account when determining the new concession period. The research aims to guide the government in enhancing concession policies, especially concerning railway project concession periods.